HIF-2α promotes epithelial-mesenchymal transition through regulating Twist2 binding to the promoter of E-cadherin in pancreatic cancer. Issue 1 (December 2016) - Yang, Jian; Zhang, Xu; Zhang, Yi; Zhu, Dongming; Zhang, Lifeng; Li, Ye; Zhu, Yanbo; Li, Dechun; Zhou, Jian
Abstract Background Epithelial-mesenchymal transition (EMT) is a dedifferentiation process that mainly involves in mesenchymal marker upregulation, epithelial maker downregulation and cell polarity loss. Related hypoxia factors play a crucial role in EMT, however, it remains few evidence to clarify the role of HIF-2α in EMT in pancreatic cancer. Method In this study, we investigated the expression of HIF-2α and E-cadherin by immunohistochemistry in 70 pancreatic cancer patients, as well as the correlation to the clinicopathologic characteristics. Then we regulated the expression of HIF-2α in pancreatic cancer cells to examine the role of HIF-2α on invasion and migration in vitro. Finally, we tested the relation of HIF-2α and EMT related proteins by Western blot and determined whether HIF-2α regulated EMT through Twist regulating the expression of E-cadherin by Chromatin immunoprecipitation (ChIP) assay. Results We found that HIF-2α protein was expressed positively in 67.1 % (47/70) of pancreatic cancer tissues and 11.4 % (8/70) of adjacent non-tumor pancreatic tissues, and there was a significant difference in the positive rate of HIF-2α protein between two groups (χ 2 = 45.549, P < 0.05). In addition, the staining for HIF-2α was correlated with tumor differentiation (P < 0.05), clinical stage (P < 0.05) and lymph node metastasis (P < 0.05), while E-cadherin expression was only correlated with lymph node metastasis (P < 0.05). HIF-2α promoted cell migration, invasion in vitro, and regulated the expression of E-cadherin and MMPs, which are critical to EMT. Our further ChIP assay suggested that only Twist2 could bind to the promoter of E-cadherin in -714 bp region site, but there is no positive binding capacity in -295 bp promoter region site of E-cadherin. Clinical tissues IHC staining showed that Twist2 and E-cadherin expression had an obviously negative correlation in pancreatic cancer. Nevertheless, it had no obvious correlation between Twist1 and E-cadherin. Conclusion These findings indicated that HIF-2α promotes EMT in pancreatic cancer by regulating Twist2 binding to the promoter of E-cadherin, which meant that HIF-2α and this pathway may be effective therapeutic targets for pancreatic cancer.